Aplicación de estrategias de educación ambiental para la conservación del barranco San Francisco - Aguila Pinedo, Mercy Miluska Del (2013)
The Moyobamba city is surrounded by ravines, the San .Francisco ravine is one of the few ravines city with conservation initiative, undertaken by the neighbors organized. The Neighborhood Association San Francisco Ecologist (A VESF) neigbborhood, organization that use the 2.48 Has the San Francisco ravine to create a botanical garden that bears the same name. The partners are adminístrate it. The partners of the A VESF pay little attention to the realization of activities that contribute to tbe conservation of the de San Francisco ravine, because they prioritize the recreational, which are the ones that generate greater incorne by renting the maín room or bungalow. The present research work had ·as its n1ain objective the implernentation of the three strategies of environrnental education to awaken interest in the conservation ofthe San Francisco ravine and in tum the finding of three hypotheses ( one for each strategy). The first strategy was "environmental traininirto the partners of the A VESF" with the aim to offer knowledge in environmental topics to wake the interest up for the conservation of the San Francisco Ravine_, poss~ssing the participation of thirteen members of the board of directors, obtaining as result that after the application of the Strategy I the partners showed major ínterestto preserve the Ravine San Francisco. The first strategy was "environmental trainíng to the partners of the A VESF" wíth the goal of providing expertise in environrnental issues for awakening the interest for the preservation ofthe San Francisco ravine, withthe}'ar:ticipatiori ofthirteen mernbers of the board of directors, obtaining as a result that a.fter the implementation of the I · strategy partners showed greater interesfin preservirig the San Francisco ravine. The second strategy was a " Environmental School " that had as airn qualify the children and teenagers of Lluy1lucucha nelghborhood in environrnental topics to wake the interest up for the conservation of the San FranciscoRavine, one possessed 20 participants, obtaining as result that after the application. of the II Strategy the participants of the Environmental School the participants showed major interest to preserve the San FranciscoRavine. The third strategy was a " Creation of an environmental club 11 which airn was to strengthen attitudes and environmental aptitudes in the partners of the A VESF and teenagers ofLluyllucucha neighborhood, to wake the interest up for the conservation of the San Francisco Ravine, being achieved to create the Environmental Club NAUCA shaped by nine members (participants ofthe Envirorunental School), obtaining as result that after the application of the TII rd Strategy the members of the environrnental NAUCA clubshowed rnajor interest to preserve the San Francisco ravine. Key words: environmental club, San Francisco Ravine.